INTERPRETATION APPROACHES THROUGH CELLO GAME TECHNIQUES IN THE "ARIOSO" SONG J.S. BACH - Viky Candra Efendy (Repertoar, 2020)
Arioso song by J.S Bach is one repertoire that is usually played in the advanced stages of cello learning. Besides that, Arioso song contains techniques that presenter may often not pay attention to in playing this work. This study aims to describe the interpretation approach through cello instrument playing techniques on the song Arioso J.S Bach. In this study, researchers used qualitative research methods. The research location was in the researcher's house, rented by the researcher, and in the library majoring in the Faculty of Languages and Arts. Data collection techniques used were observation and interviews. Data analysis techniques used include data reduction, data presentation and verification. Based on the results of this study, it can be concluded that in this song there are various techniques that must be played to be able to produce the desired interpretation including time signature, tempo, game techniques, and ornaments